Do changes in prescription practice in patients with rheumatoid arthritis treated with biological agents affect treatment response and adherence to therapy? Results from the nationwide Danish DANBIO Registry. Issue 7 (13th February 2008) - Hetland, M L; Lindegaard, H M; Hansen, A; Pødenphant, J; Unkerskov, J; Ringsdal, V S; Østergaard, M; Tarp, U
Abstract : Background: Prescription practice for tumour necrosis factor α (TNFα) inhibitors has changed towards treating patients with lower disease activity. Objective: To determine the trend in treatment response in cohorts of patients with rheumatoid arthritis who started TNFα inhibitor treatment between 2000 and 2005. Methods: 1813 patients with RA starting treatment with biological agents in 2000–5 were registered prospectively in the nationwide DANBIO Registry. Baseline disease activity and 12 months' treatment responses were determined in cohorts based on start year (2000/1; 2002; 2003; 2004; 2005). Results: Despite decreasing baseline disease activity from the 2000/2001 cohort to 2005 cohort (28-joint count Disease Activity Score (DAS28): from 5.9 to 5.3 (p<0.001)), the 12 months' DAS improvement increased from 1.8 units (2000/2001 cohort) to 2.2 units (2005 cohort) (p<0.001). The fraction with good EULAR response increased from 28% (2000/2001 cohort) to 50% (2005 cohort); the fraction with no response decreased from 29% (2000/2001 cohort) to 16% (2005 cohort). ACR20/50/70 response rates increased from 53%/31%/13% (2000/2001 cohort) to 69%/51%/30% (2005 cohort). After correction for withdrawals, treatment responses were lower, but patterns unchanged. One-year drug survival was for the 2000/2001 cohort: 73%, 2002: 62%, 2003: 67%, 2004: 70%, 2005: 69%. Conclusion: From 2000 to 2005, significantly improved treatment responses to TNF inhibitors were seen in clinical practice despite decreasing baseline disease activity levels. This lends support to the less stringent prescription practice towards treating patients with lower disease activity that has been observed in several countries.